How Much Instructional Time Is Necessary? Mid-intervention Results of Fundamental Movement Skills Training Within ABA Early Intervention Centers - Felzer-Kim, Isabella Theresa; Hauck, Janet Lynn (Frontiers in Integrative Neuroscience, 2020)
Background: The purpose of this study was to explore the question of minimally effective instructional time by assessing the efficacy at mid-intervention of an early fundamental movement skill (FMS) intervention for preschoolers with Autism Spectrum Disorder (ASD). Method: Fourteen preschoolers participated in this randomized controlled trial daily over 10 weeks (10 hours total at mid-intervention). A repeated measures MANOVA tested the significance of group*time interactions for object control, locomotor, and total motor raw scores on the Test of Gross Motor Development – III. Results: Group*time interactions approached significance with large effect sizes for both object control and total motor, but not for locomotor scores. Conclusions: These findings hold relevance for physical educators working with young children with ASD, indicating that 10 hours of FMS instruction, at least in this form, is not adequate to improve FMS.